1990
DOI: 10.1128/mcb.10.7.3709
|View full text |Cite
|
Sign up to set email alerts
|

The c-myc proto-oncogene regulates cardiac development in transgenic mice.

Abstract: During the maturation of the cardiac myocyte, a transition occurs from hyperplastic to hypertrophic growth. The factors that control this transition in the developing heart are unknown. Proto-oncogenes such as c-myc have been implicated in the regulation of cellular proliferation and differentiation, and in the heart the switch from myocyte proliferation to terminal differentiation is synchronous with a decrease in c-myc mRNA abundance. To determine whether c-myc can influence myocyte proliferation or differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(102 citation statements)
references
References 40 publications
4
98
0
Order By: Relevance
“…To our knowledge, 3 kinds of animal models for cardiac hypertrophy have been reported: spontaneously hypertensive rat (SHR) [25], syrian hamster with cardiomyopathy [26], and c-myc transgenic mice [27]. Although the mechanism causing cardiac hypertrophy in the former two animals is suspected to be in the abnormality of the cardiac cellular membrane [28,29], this is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, 3 kinds of animal models for cardiac hypertrophy have been reported: spontaneously hypertensive rat (SHR) [25], syrian hamster with cardiomyopathy [26], and c-myc transgenic mice [27]. Although the mechanism causing cardiac hypertrophy in the former two animals is suspected to be in the abnormality of the cardiac cellular membrane [28,29], this is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic overexpression of oncogenes/cell cycle promoters has led to cell cycle activation in adult cardiomyocytes but still failed to prove cell division. 27,[29][30][31][32][33] Recently, a major step forward was made by demonstrating that targeted expression of Cyclin D2 in cardiomyocytes leads to DNA synthesis in vivo and infarct regression. Although this study presents several indirect proofs for cardiomyocyte proliferation (increase in DNA synthesis, mitotic figures, and cell number based on mathematical calculations), the clear evidence that adult cardiomyocytes proliferate is still lacking.…”
Section: Can Adult Mammalian Cardiomyocytes Proliferate?mentioning
confidence: 99%
“…This might be the reason why most studies trying to induce cardiomyocyte proliferation have focused on inducers of proliferation, namely growth factors, cell cycle genes, and oncogenes. [27][28][29][30][31][32][33] However, these attempts were not successful. Based on the observation that cardiac tumors occur very rarely, this is not a surprising result.…”
Section: How Is Cardiomyocyte Proliferation Regulated?mentioning
confidence: 99%
“…Jackson et al (1990) overexpressed c-Myc during embryogenesis of mice and demonstrated both increased cardiomyocyte numbers (almost twofold) and heart weight (Jackson et al, 1990). In another study, adenoviral overexpression of oncogene E1A in cardiomyocytes resulted in induced cardiomyocyte cycling followed by apoptosis (Liu and Kitsis, 1996).…”
Section: Cardiogenic Factors Of Cardiomyocytesmentioning
confidence: 97%